2014
DOI: 10.1123/jsep.2013-0100
|View full text |Cite
|
Sign up to set email alerts
|

Body-Related Envy: A Social Comparison Perspective in Sport and Exercise

Abstract: These three studies sought to better understand experiences of body-related envy and to examine the association with motivation and exercise behavior in young adult males and females. In an interview study, participants (N = 11) discussed body-related envy within a framework of social comparison. In Study 2, a thematic content analysis was conducted on self-reported narratives of body-related envy experiences reported by 288 participants. Themes of body-related envy triggers, cognitions, and cognitive and beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 67 publications
4
35
0
1
Order By: Relevance
“…Although these findings are correlational in nature, they are gleaned from a sample of young women at the peak of their reproductive lifespan, individuals who are perhaps most likely to be affected by intrasexual competition in the mating domain. Our results converge with evidence that envy naturally occurs in women's everyday social comparisons (McKee et al 2013), physical attractiveness comparisons (DelPriore et al 2012;, body comparisons with respect to sports and exercise (Pila et al 2014), and media comparisons affecting cosmetic surgery choices (Nabi and Keblusek 2014). The finding that dispositional envy mediated links between appearance comparison and appearance enhancement motives are consistent with those of Nabi and Keblusek (2014) who found that envy mediated links between attractiveness comparison to media figures (i.e., individuals featured on makeover programs) and cosmetic surgery motives.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Although these findings are correlational in nature, they are gleaned from a sample of young women at the peak of their reproductive lifespan, individuals who are perhaps most likely to be affected by intrasexual competition in the mating domain. Our results converge with evidence that envy naturally occurs in women's everyday social comparisons (McKee et al 2013), physical attractiveness comparisons (DelPriore et al 2012;, body comparisons with respect to sports and exercise (Pila et al 2014), and media comparisons affecting cosmetic surgery choices (Nabi and Keblusek 2014). The finding that dispositional envy mediated links between appearance comparison and appearance enhancement motives are consistent with those of Nabi and Keblusek (2014) who found that envy mediated links between attractiveness comparison to media figures (i.e., individuals featured on makeover programs) and cosmetic surgery motives.…”
Section: Discussionsupporting
confidence: 80%
“…In support of this model, Pila et al (2014) found that among undergraduates, the most frequently reported trigger of body-related envy was a discrepancy in physical comparisons, and that envy predicted reported exercise motivation and behaviors. Moreover, Nabi and Keblusek (2014) found that women's self-reported comparisons with media figures were associated with greater reported intention to undergo risky cosmetic surgical procedures (e.g., botulinum toxin injections, liposuction, breast implants), and that envy (rather than hope or sadness) mediated this relationship; however, this study was limited in its focus solely on extreme appearance enhancement (i.e., cosmetic) procedures, as well as in the cross-sectional nature of its design, leaving unanswered the question of whether envy mediates a more generalized tendency among women to enhance their physical attractiveness in light of making appearance-based social comparisons.…”
Section: Envymentioning
confidence: 48%
“…Higher scores represent higher levels of dispositional body envy. The adapted version of this scale has been used in past research [43,44] and shows strong preliminary psychometric properties. 1 The Dispositional Envy Scale [42] was modified by contextualizing all items to focus on the body/physique (i.e., original item of “I feel envy every day” was modified to “When I think about my body/physique, I feel envy everyday”).…”
Section: Methodsmentioning
confidence: 99%
“…However, the current conceptualizations of social comparison tendencies are restrictive, in that they do not consider associated affect and emotion—components that have been identified as overlooked but highly relevant factors of social comparison processes [31]. For example, Sabiston and Pila [32] characterized concurrent experiences of body-related envy and shame as emotional domains of social comparisons, which uniquely contribute to women’s body-related experiences.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits that come from physical activity are indubitable (Warburton et al, 2006) and contribute to improve people's health, reducing cardiovascular diseases (Myers, 2003;Patel et al, 2013) and diabetes (Brown et al, 2014;Weisser, 2014), preventing several types of cancer and recovering from it (Foucaut et al, 2014;Keimling et al, 2014;Behrens et al, 2014;Gotte et al, 2013;Gonçalves et al, 2014;Buffart et al, 2014), improving musculoskeletal status and disability (Laskowski and Lexell, 2012) and finally potentiating physical attractiveness, well-being (Duda et al, 2014) and social experiences (Pila et al, 2014). The rates of physical activity are different across countries and regions, gender, age and socioeconomic status.…”
Section: Introductionmentioning
confidence: 98%